Highly promiscuous paternity in mainland and island populations of the endangered Northern Quoll. (30th October 2019) - Chan, R.; Dunlop, J.; Spencer, P. B. S.
Abstract: Polyandry is a commonly utilized strategy in mammalian reproductive systems, where females engage in mating with multiple males to increase either the genetic diversity or quality of their offspring. Some species also exhibit male semelparity, a peculiar life‐history trait where all or most males within a population begin to die following mating. The northern quoll ( Dasyurus hallucatus ) possesses both of these reproductive adaptations, and females of this species may produce up to eight young in a single litter. Here we aimed to quantify whether there was any difference in female quolls' choice of male sires between two genetically distinct populations located in the Pilbara region of Western Australia (one mainland‐dwelling and one island‐dwelling population). The total parentage exclusion probability was 0.9999 for excluding a candidate parent from parentage, given the genotype of a known mother. Overall, we found that every litter had young resulting from multiple males. In some litters, a different male fathered every offspring. Thus, northern quolls demonstrated a greater level of polyandry than has previously been detected in marsupials. Furthermore, females from the less genetically diverse island population exercised mate choice and preferentially bred with males that were, on average, 20% smaller than a different male randomly sampled from the island. There was no detectable difference with regard to male sire body size in the mainland population, indicating a difference of selective pressures for the two populations. Abstract : Mammals have adopted an array of reproductive strategies to increase the genetic diversity or quality of young. northern quolls, where most males die after seasonal breeding, have an extreme promiscuous form of multiple mate choice, with every young in a female's pouch has been fathered by different males. This is found in different locations on the mainland and on genetically isolated islands and has important implications for the conservation of the species.